Carbon stored in forest plantations of Pinus caribaea, Cupressus lusitanica and Eucalyptus deglupta in Cachí Hydroelectric Project - Rojas, Marilyn (2014)
Forest plantations are considered the main carbon sinks thought to reduce the impact of climate change. Regarding many species, however, there is a lack of information in order to establish metrics on accumulation of biomass and carbon, principally due to the level of difficulty and the cost of quantification through direct measurement and destructive sampling. In this research, it was evaluated carbon stocks of forest plantations near the dam of hydroelectric project Cachí, which belongs to Instituto Costarricense de Electricidad. 25 unit samples were evaluated along some plantations that contain three different species. 30 Pinus caribacea trees, 14 Cupressus lusitanica and 15 Eucalyptus deglupta were extracted. The biomass was quantified by means of the destructive method. First of all, every component of the tree was weighed separately; then, sampling was obtained in order to determine the dry matter and the carbon fraction. 110 biomass samples from the three species were analyzed in laboratory, including all the components (leaves, branches, shaft, and root). The carbon fraction varied between 47,5 and 48,0 for Pinus caribacea; between 32,6 and 52,7 for Cupressus lusitanica, and beween 36,4 and 50,3% for Eucalyptus  deglupta. The stored carbon was 230, 123, and 69 Mg ha-1 in plantations of P. caribaea, C. lusitanica and E. deglupta, respectively. Approximately, 75% of the stored carbon was detected in the shaft.